A new species and a new record of Morphosphaera Baly, 1861 (Coleoptera: Chrysomelidae: Galerucinae) from China - Ding, Chang-Ping; Shen, Jian; Yang, Xing-Ke; Yang, Mei-Xia (Zootaxa, 2026)
A new species of Morphosphaera Baly from Mêdog County, Xizang Autonomous Region is described: M. medogensis sp. nov., and a newly recorded species from China is reported: M. montivaga Maulik. Illustrations of the habitus and external genitalia of these species are provided, along with a key and a checklist of all known Morphosphaera species worldwide. And the new provincial distribution of Morphosphaera in China has been added.